TOXIC EFFECT OF A CERTAIN MEDICINAL PLANT EXTRACTS AGAINST LARVAE OF MOSQUITO SPECIES Culiseta longiareolata (MACQUART, 1838) - AISSAOUI , l; BOUAZIZ , A; BOUDJELIDA, H. (My University, 2022)
The domestic mosquito Culex pipiens and Culiseta longiareolata are considered to be the most important mosquito species in Algeria, due to their large geographical distribution and abundance. Instead of causing environmental nuisance, they transmit diseases to the animals. The mosquito control, using conventional insecticides becomes harmful to human and to the environment and in addition mosquitoes have developed a resistance against these products. These reasons have encouraged scientists to propose new eco-friendly and effective alternatives to control insects. Plants extracts have showed a promising agents for pest treatments. In order to test a botanical larvicide against mosquito, extracts were prepared from the leaves of Marrubium vulgare, Laurus nobilis, Eucalyptus globulus, and Myrtus communis and the extractions were done with methanol, using a Soxhlet extractor. Bioassay was carried out, using different concentrations against the fourth mosquito larvae of the C. longiareolata. The toxicity of the tested extracts was evaluated and the lethal concentrations, LC50 and LC90) values were estimated. The obtained results indicated a sensitivity of Cs. longiareolata larvae to the four plants species, with dose-response relationship mortality. The lethal concentrations were calculated with their confidence limits and their values were for LC50 of 6.13, 7.03, 9.60 and 17.84g/l, while the LC90’s were 22, 37.19, 75.69 and 92.76g/l for M. vulgare, L. nobilis, E. globulus, and Myrtus communis respectively. These toxicological assays, using these autochthon plant extracts could be developed as an alternative compound for mosquito control programme.